Juan Ricardo Nervi. TEACHER (Praxis Educativa, 2021)
August 19 marks the 100th anniversary of the birth of Juan Ricardo Nervi. TEACHER, pedagogue and teacher trainer. Someone who had the virtue to put his training - vocation of educator in dialogue with the most varied dimensions of culture, convinced of the strong humanistic sense of responsibility of those who educate.